Diversity and Postzygotic Evolution of the Mitochondrial Genome in Hybrids of Saccharomyces Species Isolated by Double Sterility Barrier - Szabó, Adrienn; Antunovics, Zsuzsa; Karanyicz, Edina; Sipiczki, Matthias (Frontiers in Microbiology, 2020)
Eukaryotic species are reproductively isolated by sterility barriers that prevent interspecies fertilisation (prezygotic sterility barrier) or the fertilisation results in infertile offspring (postzygotic sterility barrier). The Saccharomyces species are isolated by postzygotic sterility barriers. Their allodiploid hybrids form no viable gametes (ascospores) and the viable ascospores of the allotetraploids cannot fertilise (conjugate). Our previous work revealed that this mechanism of reproductive isolation differs from those operating in plants and animals and we designated it double sterility barrier (the failure of homeologous chromosomes to pair and the repression of mating by mating-type heterozygosity). Other studies implicated nucleo-mitochondrial incompatibilities in the sterility of the Saccharomyces hybrids, a mechanism assumed to play a central role in the reproductive isolation of animal species. In this project the mitochondrial genomes of 50 cevarum (S. cerevisiae x S. uvarum) hybrids were analysed. 62% had S. cerevisiae mitotypes, 4% had S. uvarum mitotypes, and 34% had recombinant mitotypes. All but one hybrid formed viable spores indicating that they had genomes larger than allodiploid. Most of these spores were sterile (no sporulation in the clone of vegetative descendants; a feature characteristic of allodiploids). But regardless of their mitotypes, most hybrids could also form fertile alloaneuploid spore clones at low frequencies upon the loss of the MAT-carrying chromosome of the S. uvarum subgenome during meiosis. Hence, the cevarum alloploid nuclear genome is compatible with both parental mitochondrial genomes as well as with their recombinants, and the sterility of the hybrids is maintained by the double sterility barrier (determined in the nuclear genome) rather than by nucleo-mitochondrial incompatibilities. During allotetraploid sporulation both the nuclear and the mitochondrial genomes of the hybrids could segregate but no correlation was observed between the sterility or the fertility of the spore clones and their mitotypes. Nucleo-mitochondrial incompatibility was manifested as respiration deficiency in certain meiotic segregants. As respiration is required for meiosis-sporulation but not for fertilisation (conjugation), these segregants were deficient only in sporulation. Thus, the nucleo-mitochondrial incompatibility affects the sexual processes only indirectly through the inactivation of respiration and causes only partial sterility in certain segregant spore clones.